Development of Interactive Multimedia for Indonesian Language Class VII SMPN 1 Gido - Kesaktian Telaumbanua; Riana; Hilda Natalia Hulu (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
The aim of this study is to create legitimate, usable, and efficient interactive multimedia learning tools. Research and development describes this sort of study. One such model that is utilized is the 4D model. For the creation of a wide range of educational materials, the 4D development model is an invaluable tool. There are four steps to the 4D process: defining, designing, developing, and disseminating. Interactive multimedia learning materials in the form of apps were created and tested in class VII-B at SMP Negeri 1 Gido using a validity testing stage that involved three validators, small group tests, and field tests. Interactive multimedia learning media in the form of apps has been validated by 97.5% of material and content experts, 100% of language experts, and 96.67% of design experts as valid and viable, according to the research. The questionnaire used to evaluate the practicality of application-based interactive multimedia learning material has a rating range from 1 to 4, with 4 being the most appropriate, 3 the most appropriate, 2 the least appropriate, and 1 the least appropriate. Applications using interactive multimedia learning materials that have been validated are considered viable for testing. In small group assessments, 86.67% of students found interactive multimedia learning materials to be practically applicable, while in field tests, 88.46% fell into the